Conversion of Limonene to Carvone by Oxidative Biocatalysis - Govender, Otisha (University of the Witwatersrand, Johannesburg, 2025)
Flavour and fragrances play an important role in our daily lives. R-(−)-carvone, an oxygen containing monoterpene, is the characteristic odour found in spearmint. It is commercially important and used in the baking, cosmetic and pharmaceutical industries. However, demand greatly exceeds the natural supply, and the bulk of carvone is produced synthetically. Unfortunately, the chemical synthesis of carvone from the sustainable natural compound limonene produces harmful by-products such as nitrosyl-chloride. Hence, we aimed to use biocatalysis to convert limonene to carvone in an environmentally friendly manner. We used lipoxygenase (LOX) rich soybean meal to facilitate the conversion of limonene to carvone. Two soybean preparations were compared for efficiency, ground soybean (GSB) and milled defatted soybean (MDS). GSB unfortunately produced excessive emulsions that trapped our product and made the reaction workup difficult. Since both GSB and MDS provided similar conversions, we opted to use MDS throughout going forward for ease of product extraction. Our study sought to characterise the enzyme activity and thereby confirm that LOX was indeed responsible for conversion of limonene to carvone. We found that the maximum enzyme activity occurred at the pH 8.5, using a 0.1 M sodium borate buffer. A temperature study was also conducted, and it was found that the enzyme activity was highest at 50°C and temperatures higher than this causes the enzyme to denature. Reactions excluding oxygen did not proceed, therefore we can confirm that they involve an oxidative biocatalyst that utilises molecular oxygen. The conversion was also demonstrated to require the intermediate peroxidation of fatty acids. These results are consistent with LOX activity. We decided to investigate which isozyme of LOX is responsible for the conversion. Calcium is a known inhibitor of LOX-3 activity but increases the activity of LOX-1 and LOX-2. After adding calcium salts to the reaction, the conversion rate increased. This result, and the optimal pH of 8.5, are consistent with the activity of LOX-1. It was determined that the optimal MDS to substrate ratio was 10:1. The highest conversion obtained for the reaction was at 58% when adding FeSO4.7H2O to the reaction, implying a synergistic Fenton reaction. Finally, carvone was successfully isolated and purified using column chromatography and the chemical identity confirmed using GC-MS and NMR.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2025
Keywords: Limonene; Carvone; Biocatlysis; Lipoxygenase Enzyme; Enzymes; Green Chemistry; UCTD; SDG-3: Good health and well-being; SDG-9: Industry, innovation and infrastructure